2016
DOI: 10.3126/njdvl.v14i1.15836
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Acanthosis Nigricans, A Benign Condition or Associated with Systemic Disease. A Case-Control Study

Abstract: Background: Acanthosis nigricans (AN), a common cutaneous finding, characterized by hyperpigmentation and velvety hyperplasia of the epidermis affecting flexures. Its exact prevalence varies according to age, race, degree of obesity and endocrinopathy.Objectives: Though previous studies have identified AN as marker of hyperinsulinemia and its common association with obesity, this study was done to see if AN occurs as benign condition or has any underlying disease and also to identify the possible risk factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Univariate analysis in our study depicted a significant association of AN with BMI, waist circumference, high systolic and diastolic blood pressure, HDL, TG and MS. This is in concordance with a previous case–control study 11 where univariate analysis showed a statistically significant association of high BMI, abnormal waist circumference, diastolic BP and MS with AN. Additionally, a significant association of AN noted with fasting blood sugar, while no association of AN with abnormal HDL was noted.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Univariate analysis in our study depicted a significant association of AN with BMI, waist circumference, high systolic and diastolic blood pressure, HDL, TG and MS. This is in concordance with a previous case–control study 11 where univariate analysis showed a statistically significant association of high BMI, abnormal waist circumference, diastolic BP and MS with AN. Additionally, a significant association of AN noted with fasting blood sugar, while no association of AN with abnormal HDL was noted.…”
Section: Discussionsupporting
confidence: 93%
“…Our study, on multivariate analysis, demonstrated a significant association between abnormal waist circumference, high systolic and diastolic blood pressure, and high TG levels with AN. In the previous study by Acharya et al, 11 multivariate analysis showed a significant association of abnormal waist circumference and MS with AN, while no such association was noted with abnormal HDL level.…”
Section: Discussionmentioning
confidence: 76%
“…Acharya et al in their case -control study, on univariate analysis showed a statistically significant association of fasting blood sugar (OR=3.98; CI=95;P=0.01). 16 They have not done univariate analysis of insulin, HOMA-IR. Table 6 shows week correlation of HOMA-IR with acanthosis nigricans severity with coefficient of 0.0798, which was statistically insignificant with P-value of 0.478 (P > 0.05).…”
Section: Discussionmentioning
confidence: 99%